Analisis Mengenai Pembagian Harta Bersama Pasca Perceraian Terhadap Putusan Nomor 236/Pdt.G/2020/PN Cbi - Jasmine Adhisty Fiqannawati; Meliyana Yustikarini (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Joint assets is all of every assets that is obtained during the marriage, but grants and prizes are not included joint property. When the married couple decided to divorce, the joint assets must divided into two equals part. There is an agreement that is known as marriage agreement during the marriage, that the agreement has a purpose to separate the husband’s assets and the wife’s assets, so that all of the assets that was obtained in marriage are not joint assets. The marriage agreement could be made by a Notary, but it has to be registered by a civil register to be valid for third party. It is needed to do the research about how joint property divided after the divorce based on Putusan Nomor 236/Pdt.G/2020/PN and how a Notary holds authority about the marriage agreement. This type of research is doctrinal research with constitutions approach. This research used qualitative method and literature study. The results of this research are joint assets that the marriage was carried out without a marriage agreement has to divided into two parts equally and Notary as public official has authorities not only to make marriage agreement, but also validate that marriage agreement.